Delaware Bay Shorebird-Horseshoe Crab Assessment Report and Peer Review (U.S. Fish and Wildlife Service, 2003)
This document is a peer-reviewed report that synthesizes unpublished and published information on shorebird population trends, threats to shorebird populations, shorebird habitat use, shorebird energetic requirements, and horseshoe crab egg abundance. Although several shorebird species were considered in the report, attention primarily focused on the red knot (Calidris canutus rufa). Available information was greatest for the red knot and was less extensive for the ruddy turnstone, sanderling, semipalmated sandpiper, and least sandpiper. Aside from the least sandpiper, which was chosen because of its contrasting use of marsh habitats, all other species were selected because of their reliance on beach habitats and their frequency of occurrence on Delaware Bay aerial surveys. The report lists conclusions, management recommendations, and information needs. Prepared for the Atlantic States Marine Fisheries Commission. U.S. Fish and Wildlife Service Migratory Bird Publication R9-03/02